Manfaat Cangkang Sawit Sebagai Bahan Bakar Ketel Uap Pada Pabrik CPO - Lelawati lelawati (MAJALAH TEKNIK SIMES, 2020)
Abstract Steam boilers are devices that work by heating water to boiling and producing high-pressure hot steam, heat energy or often called heat can be used for oil palm boiling processes at CPO mills. Heating Value is chemical energy released by fuel during the combustion process. Fuel value consists of two types, namely: Highest Heating Value (HHV) Low fuel value (Lowest Heating Value / LHV) Low fuel calorific value is the amount of heat obtained in perfect combustion of 1kg of fuel without taking into account the heat condensation of water vapor on the fuel.